Dual-effects of carbon doping on the recrystallization kinetics of the Cantor alloy during mid-temperature annealing. (April 2023) - Chen, Wentian; Wu, Yufan; Guo, Lin; Gu, Ji; He, Junyang; Song, Min
Abstract: In this study, the comprehensive effects of carbon doping on the recrystallization process and the corresponding mechanical performance of the Cantor alloy during mid-temperature (700 °C) annealing were investigated. In the early stage of recrystallization, i.e., before 7 min annealing, abundant M23 C6 carbides form preferentially along deformation bands and hence accelerate recrystallization process by providing dense heterogeneous nucleation sites. The fast consuming of the stored defects by recrystallization in this stage leads to the drastic decrease of strength but the regain of ductility. Detailed characterization on the precipitation behavior further shows that the initial fine carbide (≤10 nm in size) firstly enriches in carbon only, and then gradually grows to perfect M23 C6 as controlled by the diffusion of Cr. In the later stage of recrystallization, e.g., after 7 min annealing, these carbides coarsen and Zener-pin grain boundaries from further migration, which in turn suppress the overall recrystallization process. In this stage the mechanical properties vary slightly as a result of the balance between the slowly deceased amount of hard non-recrystallized regions and the slowly increased carbide volume fraction. Graphical abstract: Image 1 Highlights: Carbon-doping shows dual-effects on recrystallization kinetics of the Cantor alloy. Before 7 min, recrystallization process is accelerated by more nucleation sites. After 7 min, recrystallization process is suppressed by M23 C6 carbide pinning. Cr gradually enriches accompanied with growth of the M23 C6 carbide.